Support Vector Machine, Multilayer Perceptron Neural Network, Bayes Net And K-Nearest Neighbor In Classifying Gender Using Fingerprint Features - Abdullah , Siti Fairuz; Abdul Rahman, Ahmad Fadzli Nizam; Abal Abas, Zuraida; Mohd Saad, Wira Hidayat (IJCSIS, 2016)
-